Operation and control of PEM fuel cell system - Tan, Chun Xu. (2013)
Microgrid systems are the modern versions of the centralized electricity system and have become a possible way to integrate renewable resources on the community level. Smart Microgrids will generate, distribute, and monitor the flow of electricity at the local community level, unlike the conventional bulk power grid. Hence, the use of the fuel cell based power system for residential or industrial application is expected to be more prevalent in the near future due to improved power quality, reliability, portability and sustainability of the ecology system. However, integration of a variety of small-size distributed generators is changing the traditional structure of electric power distribution systems and affecting system dynamics, whose main source of power supply is the substation.